2023
DOI: 10.1093/zoolinnean/zlad136
|View full text |Cite
|
Sign up to set email alerts
|

Tardigrade diversity and community composition across Norwegian boreal forests

Roberto Guidetti,
K Ingemar Jönsson,
Łukasz Kaczmarek
et al.

Abstract: Tardigrades are common in many terrestrial environments and habitats. Although little is known on their ecological preferences, previous studies found diversity and community composition significantly affected by various variables. This study associated tardigrade species’ records with climatic variables, forest type, and substrate categories exploring tardigrade diversity and species communities to find associations with ecological characteristics of Norwegian forests. A total of 17 473 specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 89 publications
4
3
0
Order By: Relevance
“…As in some previous studies (Guidetti et al., 2024 ; Jönsson, 2003 ; Mäenpää et al., 2023 ), we found (Table 1 ) the highest tardigrade densities in the moss group Hypnales (the feather mosses Pleurozium schreberi and Hylocomnium splendens ), which are commonly found in the hummocks of more wooded peatland types. Over 80% of the identified specimens in Hypnales mosses were omnivorous, of which most belonged to the family Macrobiotidae (Figures 2 and 3 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As in some previous studies (Guidetti et al., 2024 ; Jönsson, 2003 ; Mäenpää et al., 2023 ), we found (Table 1 ) the highest tardigrade densities in the moss group Hypnales (the feather mosses Pleurozium schreberi and Hylocomnium splendens ), which are commonly found in the hummocks of more wooded peatland types. Over 80% of the identified specimens in Hypnales mosses were omnivorous, of which most belonged to the family Macrobiotidae (Figures 2 and 3 ).…”
Section: Resultssupporting
confidence: 89%
“…In contrast, a recent study by Guidetti et al. ( 2024 ) found a positive correlation between species richness of tardigrades and increased rainfall in mosses in a study across boreal forests in different regions of Norway. Altogether, studies have shown contrasting results of the connection between moisture and tardigrade occurrence, and it is likely to affect species differently depending on, for example, their anhydrobiosis ability.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Similar to our result, studies in Costa Rica [82] and in Great Smoky Mountains National Park (USA) [83] also showed no significant differences in estimates of tardigrade diversity between mosses and lichens, including species richness and the Shannon index. Moreover, in a study by Guidetti et al [84], similar to our study, most species were recorded in mosses and lichens, with only a comparatively small number found in cryptogams (mosses mixed with lichens). However, they also concluded that there was a considerable heterogeneity in species richness for some of the habitats, as well as noted the poor effects of habitat categories on species richness in the multiple regression, where other environmental variables were controlled [84].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, in a study by Guidetti et al [84], similar to our study, most species were recorded in mosses and lichens, with only a comparatively small number found in cryptogams (mosses mixed with lichens). However, they also concluded that there was a considerable heterogeneity in species richness for some of the habitats, as well as noted the poor effects of habitat categories on species richness in the multiple regression, where other environmental variables were controlled [84]. When comparing species diversity across different sampling substrates (i.e., concrete walls, ground surface, trees and dead wood), we have found there to be in general no significant differences between different substrates.…”
Section: Discussionsupporting
confidence: 89%